Metal-free mechanochemical oxidations in Ertalyte® jars - Porcheddu, Andrea; Delogu, Francesco; De Luca, Lidia; Fattuoni, Claudia; Colacino, Evelina (Beilstein Journal of Organic Chemistry, 2019)
Aimed at eliminating or at least significantly reducing the use of solvents, sodium hypochlorite pentahydrate crystals (NaOCl·5H2O) in the presence of a catalytic amount of a nitrosyl radical (TEMPO or AZADO) have been successfully used to induce mechanochemical oxidative processes on several structurally different primary and secondary alcohols. The proposed redox process is safe, inexpensive and performing effectively, especially on the macroscale. Herein, an Ertalyte® jar has been successfully used, for the first time, in a mechanochemical process.
Keywords: AZADO; Ertalyte®; green chemistry; mechanochemistry; NaOCl·5H2O; selective oxidation; TEMPO

Comprehensive Organic Transformations: A Guide to Functional Group Preparations - Dubrovskiy, A. V.; Kesharwani, T.; Markina, N. A.; Pletnev, A. A.; Raminelli, C.; Yao, T.; Zeni, G.; Zhang, L.; Zhang, X.; Rozhkov, R.; Larock, R. C. (John Wiley and Sons, 2018)

March's Advanced Organic Chemistry: Reactions, Mechanisms, and Structure - Smith, B. M. (John Wiley & Sons, 2013)

(untitled) - Zhang, Z.; Gao, J.; Xia, J.-J.; Wang, G.-W. (Org. Biomol. Chem., 2005)

Oxidizing and Reducing Agents - Burke, S. D.; Danheiser, R. L. (John Willey & Sons, 1999)

Oxidation of Alcohol to Aldehyde and Ketones - Tojo, G.; Fernández, M. (Springer, 2006)

(untitled) - Lebedev, O. A.; Kazarnovskii, S. N. T. (Khim. Tekhnol., Gorky, 1959)

(untitled) - Lebedev, O. L.; Kazarnovskii, S. N. T. (Zh. Obshch. Khim., 1960)

(untitled) - Merbouh, N.; Bobbitt, J. M.; Brückner, C. (J. Org. Chem., 2004)

(untitled) - Beejapur, H. A.; Zhang, Q.; Hu, K.; Zhu, L.; Wang, J.; Ye, Z. (ACS Catal., 2019)
and references cited therein.

(untitled) - Anelli, P. L.; Biffi, C.; Montanari, F.; Quici, S. (J. Org. Chem., 1987)

(untitled) - Bolm, C.; Magnus, A. S.; Hildebrand, J. P. (Org. Lett., 2000)

(untitled) - Dabral, S.; Wotruba, H.; Hernández, J. G.; Bolm, C. (ACS Sustainable Chem. Eng., 2018)

(untitled) - Einhorn, J.; Einhorn, C.; Ratajczak, F.; Pierre, J.-L. (J. Org. Chem., 1996)

(untitled) - Jing, Y.; Daniliuc, C. G.; Studer, A. (Org. Lett., 2014)

(untitled) - Li, X.-Q.; Zhang, C. (Synthesis, 2009)

(untitled) - Miller, R. A.; Hoerrner, R. S. (Org. Lett., 2003)

(untitled) - Sahoo, P. K.; Bose, A.; Mal, P. (Eur. J. Org. Chem., 2015)

(untitled) - Dabral, S.; Hernández, J. G.; Kamer, P. C. J.; Bolm, C. (ChemSusChem, 2017)

(untitled) - Parmeggiani, C.; Cardona, F. (Green Chem., 2012)

(untitled) - Allen, S. E.; Walvoord, R. R.; Padilla-Salinas, R.; Kozlowski, M. C. (Chem. Rev., 2013)

(untitled) - Cao, Q.; Dornan, L. M.; Rogan, L.; Hughes, N. L.; Muldoon, M. J. (Chem. Commun., 2014)

(untitled) - Hoover, J. M.; Ryland, B. L.; Stahl, S. S. (J. Am. Chem. Soc., 2013)

(untitled) - Ochen, A.; Whitten, R.; Aylott, H. E.; Ruffell, K.; Williams, G. D.; Slater, F.; Roberts, A.; Evans, P.; Steves, J. E.; Sanganee, M. J. (Organometallics, 2019)

Liquid Phase Aerobic Oxidation Catalysis: Industrial Applications and Academic Perspectives - Stahl, S. S.; Alsters, P. L. (Wiley-VCH Verlag GmbH, 2016)

(untitled) - Wang, L.; Shang, S.; Li, G.; Ren, L.; Lv, Y.; Gao, S. (J. Org. Chem., 2016)

Ball Milling Towards Green Synthesis: Applications, Projects, Challenges - Cravotto, G.; Calcio Gaudino, E. (Oxidation and Reduction by Solid Oxidants and Reducing Agents using Ball-Milling, 2015)

(untitled) - Andersen, J.; Mack, J. (Green Chem., 2018)

(untitled) - Bolm, C.; Hernández, J. G. (Angew. Chem., Int. Ed., 2019)

(untitled) - Do, J.-L.; Friščić, T. (ACS Cent. Sci., 2017)

(untitled) - Užarević, K.; Ferdelji, N.; Mrla, T.; Julien, P. A.; Halasz, B.; Friščić, T.; Halasz, I. (Chem. Sci., 2018)

Practical Considerations in Mechanochemical Organic Synthesis - Margetić, D.; Štrukil, V. (Elsevier, 2016)

(untitled) - Michalchuk, A. A. L.; Tumanov, I. A.; Boldyreva, E. V. (CrystEngComm, 2019)

(untitled) - Piras, C. C.; Fernández-Prieto, S.; De Borggraeve, W. M. (Nanoscale Adv., 2019)

(untitled) - Tan, D.; García, F. (Chem. Soc. Rev., 2019)

(untitled) - Tan, D.; Loots, L.; Friščić, T. (Chem. Commun., 2016)

(untitled) - Mack, J.; Fulmer, D.; Stofel, S.; Santos, N. (Green Chem., 2007)

(untitled) - Li, A. Y.; Segalla, A.; Li, C.-J.; Moores, A. (ACS Sustainable Chem. Eng., 2017)

(untitled) - Andersen, J.; Brunemann, J.; Mack, J. (React. Chem. Eng., 2019)

(untitled) - Colacino, E.; Porcheddu, A.; Charnay, C.; Delogu, F. (React. Chem. Eng., 2019)

(untitled) - Colacino, E.; Carta, M.; Pia, G.; Porcheddu, A.; Ricci, P. C.; Delogu, F. (ACS Omega, 2018)

(untitled) - Colacino, E.; Porcheddu, A.; Halasz, I.; Charnay, C.; Delogu, F.; Guerra, R.; Fullenwarth, J. (Green Chem., 2018)

(untitled) - Porcheddu, A.; Delogu, F.; De Luca, L.; Colacino, E. (ACS Sustainable Chem. Eng., 2019)

(untitled) - De Luca, L.; Giacomelli, G.; Porcheddu, A. (Org. Lett., 2001)

(untitled) - Gaspa, S.; Porcheddu, A.; Valentoni, A.; Garroni, S.; Enzo, S.; De Luca, L. (Eur. J. Org. Chem., 2017)

(untitled) - Martina, K.; Rotolo, L.; Porcheddu, A.; Delogu, F.; Bysouth, S. R.; Cravotto, G.; Colacino, E. (Chem. Commun., 2018)

(untitled) - Mocci, R.; Luca, L. D.; Delogu, F.; Porcheddu, A. (Adv. Synth. Catal., 2016)

(untitled) - Porcheddu, A.; Colacino, E.; Cravotto, G.; Delogu, F.; De Luca, L. (Beilstein J. Org. Chem., 2017)

(untitled) - Rightmire, N. R.; Hanusa, T. P. (Dalton Trans., 2016)

Microbiology of Waterborne Diseases - Gray, N. F. (Free and Combined Chlorine, 2014)

(untitled) - de Nooy, A. E. J.; Besemer, A. C.; van Bekkum, H. (Tetrahedron, 1995)

(untitled) - Naik, N.; Braslau, R. (Tetrahedron, 1998)

(untitled) - Sheldon, R. A.; Arends, I. W. C. E.; ten Brink, G.-J.; Dijksman, A. (Acc. Chem. Res., 2002)

(untitled) - Konnert, L.; Gauliard, A.; Lamaty, F.; Martinez, J.; Colacino, E. (ACS Sustainable Chem. Eng., 2013)

(untitled) - Konnert, L.; Dimassi, M.; Gonnet, L.; Lamaty, F.; Martinez, J.; Colacino, E. (RSC Adv., 2016)

(untitled) - Tan, D.; Friščić, T. (Eur. J. Org. Chem., 2018)

(untitled) - Cruz-Cabeza, A. J.; Karki, S.; Fábián, L.; Friščić, T.; Day, G. M.; Jones, W. (Chem. Commun., 2010)

(untitled) - Friščić, T. (J. Mater. Chem., 2010)

Sodium hypochlorite pentahydrate (NaOCl·5H2O, S0939) is commercially available from TCI chemicals

(untitled) - Hirashita, T.; Sugihara, Y.; Ishikawa, S.; Naito, Y.; Matsukawa, Y.; Araki, S. (Synlett, 2018)

(untitled) - Okada, T.; Asawa, T.; Sugiyama, Y.; Iwai, T.; Kirihara, M.; Kimura, Y. (Tetrahedron, 2016)

(untitled) - Okada, T.; Asawa, T.; Sugiyama, Y.; Kirihara, M.; Iwai, T.; Kimura, Y. (Synlett, 2014)

(untitled) - Watanabe, A.; Miyamoto, K.; Okada, T.; Asawa, T.; Uchiyama, M. (J. Org. Chem., 2018)

(untitled) - Wang, M.-L.; Huang, T.-H. (Chem. Eng. Commun., 2007)